Kepribadian Agreeableness Sebagai Moderasi Efikasi Diri Pengetahuan Terhadap Manajemen Pengetahuan - Nur Laily; Prijati Prijati; Kasrowi Ahmad (Faculty of Economic and Business, 2021)
Knowledge management has an important role in economic growth, therefore every organization needs to focus on knowledge for the development of its business. This study examines the influence of knowledge Self Efficacy on Knowledge Management, with Agreeableness personality as a moderating variable. Probability Sampling Simple Random Sampling is a technique used in this study. There were 98 employees at manufacture companies in Surabaya as respondents in this study. Data analysis using PLS-SEM approach. The results of the research test showed that Knowledge Self Efficacy has an effect on Agreeableness personality and Knowledge Management. However, Agreeableness personality is able to moderate Knowledge Self Efficacy towards Knowledge Management. This research also has important practical implications for companies regarding the importance of implementing knowledge self efficacy and personality of Agreeableness personality due to their proven ability to Improve knowledge management and result in increased Organizational Performance.Cara Mengutip:Laily, N., Prijati., & Ahmad, K. (2021). Kepribadian Agreebleness Sebagai Moderasi Efikasi Diri Pengetahuan Terhadap Manajemen Pengetahuan. Esensi: Jurnal Bisnis dan Manajemen, 11(1), xx-xx. https://doi.org/10.15408/ess.v11i1.20341.